(untitled) (Journal Of Educational and Psychological Researches, 2023)
Abstract The current research aims to examine the effectiveness of a training program for children with autism and their mothers based on the Picture Exchange Communication System to confront some basic disorders in a sample of children with autism. The study sample was (16) children with autism and their mothers in the different centers in Taif city and Tabuk city. The researcher used the quasi-experimental approach, in which two groups were employed: an experimental group and a control group. Children aged ranged from (6-9) years old. In addition, it was used the following tools: a list of estimation of basic disorders for a child with autism between (6-9) years, and a training program for children with autism and their mothers, they were prepared by the researcher. The results revealed that there were statistically significant differences between the mean scores of the members of the experimental and control groups in the post-measurement on the Questionnaire of Basic Disorders in Autistic Children in favor of the members of the experimental group. In addition, there are statistically significant differences between the mean scores of the experimental group members in the pre and post-measurements on the Disorders Questionnaire on the basic characteristics of autistic children in favor of the post-measurement. There were no statistically significant differences between the mean scores of the experimental group members in the post and tracer measurements on the Questionnaire of Basic Disorders in Autistic Children. The study recommended training mothers on the Pictures exchange program, and various training programs that seek to develop the skills of their children, and how to apply them with autistic children, as well as expanding the adoption of the use of the Pictures exchange system in centers for children with autism. It suggested conducting studies similar to the current study, dealing with the effect of using training programs based on positive behavior support, and its impact on reducing abnormal behaviors.